A Study of the Skeletal Remains and Burial Rituals in Cham Papi Cemetery - lily Niakan (Iranian Journal of Archaeological Studies, 2018)
During the past decade, archaeological studies conducted in the Seymareh River catchment area have provided invaluable findings for analytical investigations and, thus, gaining insights into various fields such as pottery, architecture, and multifarious cultural artefacts. Amongst the most significant of such archaeological findings are cemeteries with their cultural implications, which provide researchers—and particularly archaeologists—with an ample amount of knowledge on various aspects of ancient peoples’ lives, including the ideological, social, and economic structures and patterns of their societies. This article reports a study conducted on Cham Papi Cemetery, located in the middle of the Seymareh River catchment area. The said cemetery was discovered in the years 2014-2015 in the course of archaeological investigations, upon which researchers embarked upon exploratory endeavours aimed at identifying different cultural horizons and circumstances of this area during the proto-historic and historic periods. The main purpose of the study was to identify various habitat patterns and life circumstances in the Kaferi Strait (Tangeh Kaferi) during the proto-historic period by investigating the structures of the graves and the remnants of the human skeletons detected in this cemetery. Based on the existing evidence as well as the evaluations conducted through initial assessment of pottery exhibits, observation, documentation, and investigation of the environmental features, a purposeful excavation was initiated in 2017. The primary results concerning the remnants of this cemetery included an accurate map of the cemetery and a recognized style of grave structures and burial rituals in the Bronze Age. The pottery exhibits showed that Cham Papi Cemetery had been founded in the third millennium B.C., and it had been in use up until the beginning of the first millennium B.C. This article aims to present a summary of the key findings about the architectural structures as well as the cultural and anthropological features of Cham Papi Cemetery.